Pertanggung Jawaban Hukum bagi Notaris yang Tidak Saksama dalam Penyerahan Sertifikat Tanpa Persetujuan Para Pihak: (Studi Kasus Putusan PN 196/PID.B/PN DPS) - Risquita Putri Raco; Tetti Samosir; Indah Harlina (CV Rewang Rencang, 2025)
This study discusses the liability of a Notary, acting as a public official, in relation to the embezzlement of land ownership certificates entrusted to them during the process of a binding sale and purchase agreement. The issue arises when the Notary fails to hand over the certificate to the rightful party, thereby creating opportunities for misuse and resulting in legal harm. The purpose of this study is to analyze the elements of the criminal act of embezzlement as stipulated in Article 372 of the Indonesian Penal Code (KUHP) in connection with the Notary's responsibility, and to examine the legal protection available to parties who suffer losses due to the Notary’s lack of due care. This thesis employs a normative juridical method with a statutory approach, literature review, and case study based on court decisions. The findings show that a Notary can be held legally accountable—criminally, civilly, or administratively— if proven to have committed embezzlement or been negligent in the exercise of their authority. Storing land certificates without a legal basis or in bad faith constitutes a violation of the Notary’s obligations as regulated under the Notary Office Law (UUJN) and the Notarial Code of Ethics. The conclusion drawn from this research is that Notaries bear legal responsibility for documents entrusted to them, particularly in upholding trust and ensuring legal certainty for all parties involved. Strengthening oversight and the enforcement of sanctions is necessary to prevent abuse of authority by Notaries.